2008
DOI: 10.1007/s00262-008-0602-6
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of CD4+CD25high T cells in response to Sirolimus requires activation of T cell receptor and is modulated by IL-2

Abstract: Targeted molecular therapies inhibit cancer cell proliferation and survival but may interfere with proliferation and survival of lymphoid cells. Treatment with Sirolimus or Sorafenib was cytotoxic to CD4 + CD25 high T cells, and was growth inhibitory for CD4 + and CD8 + T cells. The cytotoxicity depended on CD3/CD28 stimulation and was detectable as early as 12 hours post-treatment, with 80 −90% of the CD4 + CD25 high T cells killed by 72 hours. Cell death was due to apoptosis, based on time-dependent increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 29 publications
2
21
2
Order By: Relevance
“…However, most results supporting this statement have been obtained with anti-VEGF mAb or the tyrosine kinase inhibitor, sunitinib. Preliminary results showed that this activity of some antiangiogenic on the immune system could not be extended to all antiangiogenic molecules [61,142]. It suggests that the current dogma regarding VEGF as the main target of antiangiogenic for the reversal of immunosuppression has to be questioned.…”
Section: Discussionmentioning
confidence: 87%
“…However, most results supporting this statement have been obtained with anti-VEGF mAb or the tyrosine kinase inhibitor, sunitinib. Preliminary results showed that this activity of some antiangiogenic on the immune system could not be extended to all antiangiogenic molecules [61,142]. It suggests that the current dogma regarding VEGF as the main target of antiangiogenic for the reversal of immunosuppression has to be questioned.…”
Section: Discussionmentioning
confidence: 87%
“…29,36 With respect to the effect of other antiangiogenic molecules on regulatory T cells, variable results were reported. 36,43,44 The targeting of molecules other than VEGF by some antiangiogenic drugs may explain this heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, mitochondrial membranes can depolarize, production of caspase 3 can be up-regulated, and the intrinsic pathway of cellular apoptosis can be stimulated [206]. The net consequence of mTOR inhibition is an impairment of the cellular immune response [207] (Fig. 1).…”
Section: Rapamycinmentioning
confidence: 98%
“…Importantly, regulatory (CD4 + CD25 + ) T cells are resistant to the apoptosis induced by rapamycin, and they are advantaged by the drug [209]. Their preferential survival is mediated by IL-2, and rapamycin is maximally effective during periods of active antigenic stimulation and IL-2 production [207]. The selective survival of the regulatory T cell population further suppresses the adaptive immune response.…”
Section: Rapamycinmentioning
confidence: 98%